Global Warming and Mass Extinctions Associated With Large Igneous Province Volcanism - Bond, David P. G.; Sun, Yadong (Large Igneous Provinces: A Driver of Global Environmental and Biotic Changes, 2021)
The coincidence of large igneous province (LIP) eruptions with at least three, if not all, of the Big Five biotic crises of the Phanerozoic implies that volcanism is a key driver of mass extinctions. Many LIP-induced extinction scenarios invoke global warming, caused primarily (but not exclusively) by greenhouse gases emitted at the site of LIP emplacement and by contact metamorphism of carbon-rich host rocks. Here we explore (1) the climate-changing products of volcanism including sulfur dioxide (SO2), carbon dioxide (CO2) and methane (CH4) from eruptions, contact metamorphism, and melting (dissociation) of gas hydrates; (2) their deadly effects, including marine anoxia and thermal stress; (3) increasingly sophisticated paleotemperature proxies (e.g., delta(1)(8)Oof shell material) through case studies of the best-known LIP-warming-extinction nexi; and (4) global warming through the lens of the putative Anthropocene extinction.
CRIS-Team WoS Importer:2022-12-02